Influence of active layer thickness on photovoltaic performance of PTB7:PC70BM bulk heterojunction solar cell - Sharma, Nidhi; Gupta, Saral K.; Singh Negi, Chandra Mohan (Superlattices and microstructures, 2019)
In this paper, we studied the effect of active layer thickness on the photovoltaic performance of inverted bulk heterojunction (BHJ) organic solar cell (OSC). The capacitance-voltage (C–V), dark current-voltage (I–V) and impedance spectroscopy (IS) analysis were carried out to explain the active layer thickness dependence on the photovoltaic performance. The OSC with an active layer thickness of 150 nm achieved the best power conversion efficiency (PCE) of 5.87%, while the OSC of 200 nm active layer thickness yielded the worst PCE. Reduction in the fill factor (FF) was the main reason for the reduction in the PCE at large active layer thickness. The dark I–V analysis revealed large defect density for the OSC with active layer thickness of 200 nm, which raised the charge recombination and leakage current and consequently reduced the FF. IS analysis predicted that the charge transport became the serious limitations for the OSC with 200 nm thick active layer, which can be attributed to the weakening of electric field as well as creation of field-free regions. It mainly caused a drastic drop in the fill factor by reducing the charge collection efficiency, consequently deteriorated the photovoltaic performance. •At large active layer thickness, high defect density causes reduction in JSC.•Recombination and leakage current strongly influences the VOC and FF of OSCs.•Reduction in FF was the main reason for the decline in PCE for thicker active layer.•Correlation between photovoltaic performance and IS parameters are established.